Evaluation of the safety of ethanolic extract from Piper amalago L. (Piperaceae) leaves in vivo: Subacute toxicity and genotoxicity studies - Stein, Julia [UNESP]; Jorge, Bárbara Campos [UNESP]; Casali Reis, Ana Carolina [UNESP]; Santos Radai, Joyce Alencar; da Silva Moreira, Suyane [UNESP]; Fraga, Thiago Leite; da Silva Mota, Jonas; Oliveira, Rodrigo Juliano; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Elsevier, 2022)
Piper amalago L. (Piperaceae) is traditionally used due to its anti-inflammatory, analgesic, diuretic, and antiparasitic properties. However, few studies have focused on its adverse effects, compromising its safe use. This study evaluated the toxicological safety of ethanolic extract from Piper amalago leaves (EEPA), through subacute toxicity and genotoxicity assays in rodents. In subacute toxicity, 100, 200 or 300 mg/kg of EEPA were tested in female Wistar rats, by gavage, for 28 days. For genotoxicity test, female Swiss mice were orally treated with 17.5, 175 or 1750 mg/kg of EEPA and the comet, micronucleus, and splenic phagocytic assays were evaluated. In subacute toxicity, the extract induced an increase in the food and water intakes, as well as in the liver absolute weight, and in the heart and kidney relative weights. EEPA also provoked alterations in histopathological analysis of liver and in hemato-biochemical parameters, evidenced by a decrease in hematocrit levels and albumin levels, and an increase in the number of platelets and in alkaline phosphatase and cholesterol levels. However, EEPA did not presented genotoxic nor mutagenic properties. EEPA showed hemato-biochemical toxicity profile in rats and should be used with caution, especially when for prolonged period.
Keywords: Genotoxicity; Hemato-biochemical alterations; Hepatotoxicity; Mice; Piper amalago; Piperaceae; Rats; Safety; Subacute toxicity